Faecal calprotectin is not necessarily required as a screen for significant bowel disease in primary care. (May 2022) - Waite, Matthew Malcolm Andrew; Langmead, Louise; Ayling, Ruth M
Objective: NICE recommends measurement of faecal haemoglobin (f-Hb) using faecal immunochemical test (FIT) when colorectal cancer is suspected and calprotectin (f-Cal) in the context of inflammatory bowel disease, though neither is disease specific. During the COVID-19 pandemic, f-Hb has been a requirement prior to referral for endoscopy in England; f-Cal is often performed simultaneously. The aim of this study was to investigate test performance of both tests for significant bowel disease in those patients referred. Design: All adult patients with simultaneous measurements of f-Hb and f-Cal between April 2019 and September 2020 were included. For those referred, outcomes were determined from clinical records. Results: 650 patients with simultaneous samples for f-Hb an f-Cal were managed in Primary Care; 319 patients were referred to hospital; SBD was found in 32 (10.0%) (CRC 5, high risk adenomas 5, IBD 22). At a cut-off of 10 μg/g for f-Hb and 200 μg/g for f-Cal, the sensitivity, specificity and negative predictive value for diagnosis of SBD were 84.4%, 58.2% and 96.7% and 68.8%, 89.6% and 95.7%, respectively. Performance of both tests would have enabled diagnosis of two more cases of significant, but non-malignant, bowel disease but required over 4% more referrals for investigation. Conclusion: Use of FIT has become established to assist prioritisation of patients for referral from Primary Care. Whilst introduced specifically for CRC, FIT performs well as a rule out for IBD in Primary Care and the use of f-Cal is not required.